2016
DOI: 10.5530/ogh.2017.6.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Cirrhosis–An Uncommon Manifestation of Common Disease

Abstract: Background: Chronic Right Heart failure is known to cause Liver Cirrhosis but it is rare. Here we are reporting the case of cardiac cirrhosis presented to us with signs of Liver Failure. Case Report : 50 year male, farmer, chronic smoker presented with progressive abdominal distension and episodes of malena since 6 months and an episode of hematemasis. On work up Liver cirrhosis was diagnosed but cause for cirrhosis was not established and on general examination pulse was irregular and features of pulmonary hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In contrast to primary PH that carries a poor prognosis and has limited treatment options, PH due to Graves' disease carries a good prognosis, with prior reports of resolution after appropriate treatment [3, 6, 11, 14], emphasizing the importance of early recognition. Also, it is very rare for hyperthyroidism-driven heart failure to lead to cirrhosis, and cirrhosis has been reported mostly in chronic right heart failure [18]. Unlike cirrhosis caused by alcohol or viral hepatitis, the effect of cardiac cirrhosis on overall prognosis has not been clearly established [18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to primary PH that carries a poor prognosis and has limited treatment options, PH due to Graves' disease carries a good prognosis, with prior reports of resolution after appropriate treatment [3, 6, 11, 14], emphasizing the importance of early recognition. Also, it is very rare for hyperthyroidism-driven heart failure to lead to cirrhosis, and cirrhosis has been reported mostly in chronic right heart failure [18]. Unlike cirrhosis caused by alcohol or viral hepatitis, the effect of cardiac cirrhosis on overall prognosis has not been clearly established [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is very rare for hyperthyroidism-driven heart failure to lead to cirrhosis, and cirrhosis has been reported mostly in chronic right heart failure [18]. Unlike cirrhosis caused by alcohol or viral hepatitis, the effect of cardiac cirrhosis on overall prognosis has not been clearly established [18, 19]. By this case, we want to highlight the importance of considering hyperthyroidism early on in the differential for unexplained valvular regurgitation and heart failure and also considering cardiac cause as a differential for liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1953, Kowalski and Abelmann first documented abnormal cardiac functions in patients with liver cirrhosis (3). Since then, a series of animal models and clinical studies have confirmed further that myocardial contractility and stimulation in patients with cirrhosis are weakened, where in severe cases heart failure can occur (4)(5)(6). This condition is known as cirrhotic cardiomyopathy (CCM) (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a series of animal models and clinical studies have confirmed further that myocardial contractility and stimulation in patients with cirrhosis are weakened, where in severe cases heart failure can occur (4)(5)(6). This condition is known as cirrhotic cardiomyopathy (CCM) (4)(5)(6). Previous studies have shown that echocardiography (ECG) can be used to evaluate left ventricular diastolic functions in patients with cirrhosis (7,8).…”
Section: Introductionmentioning
confidence: 99%